The effect of blood transfusion on serum hepcidin levels in chronically transfused patients of β-thalassemia major: An observational study in a tertiary care centre in Western Maharashtra - Sujay Bhowmik; Amit Kumar Biswas; Ajay Kumar Baranwal; Amit Ajay Pawar; Ujjwal Dimri (Asian Journal of Transfusion Science)
INTRODUCTION: Hepcidin is the key regulator of systemic iron homeostasis. In iron-loading anemias, hepcidin levels are regulated by opposite forces of erythropoiesis and iron overload. In β-thalassemia major patients, transfusions are the predominant cause of iron overload; in such chronically transfused patients, hepcidin concentrations are significantly higher than nontransfused patients, due to both increased iron load of transfusions and the suppression of ineffective erythropoiesis. AIM: This study aims to evaluate the effect of blood transfusions on serum hepcidin levels in chronically transfused patients of β-thalassemia major and correlate with hemoglobin and serum ferritin levels of pre- and posttransfusion. MATERIALS AND METHODS: Thirty-three β-thalassemia major patients requiring monthly transfusions were included in the study. Blood samples, collected pretransfusion and 7 days posttransfusion, were evaluated for hemoglobin, serum ferritin, and serum hepcidin using enzyme immunoassay. STATISTICAL ANALYSIS: Data were statistically analyzed through SPSS software and P < 0.05 is considered statically significant. RESULTS: Posttransfusion levels of hemoglobin, serum ferritin, and serum hepcidin increased. Posttransfusion levels of hepcidin were near normal levels. Pre- and posttransfusion hepcidin concentrations were significantly associated with hemoglobin levels. CONCLUSION: Serum hepcidin concentrations vary depending on the degree of erythropoiesis drive and level of anemia. We found that the serum hepcidin levels decrease over the inter-transfusion interval and transfusions cause suppression of ineffective erythropoiesis by the increase in hemoglobin. Posttransfusion values of hepcidin in our study were closer to normal levels which may be due to lower erythropoietic drive posttransfusion. We suggest that the measurement of serum hepcidin in chronically transfused β-thalassemia patients can be used as a follow-up investigation for better management of these patients.